Listening to Community: Towards Best Research Practices in Pond Inlet, Nunavut - Spiers, Kent Gordon (Graduate Studies, 2024)
What are the specific conditions and circumstances that can either prevent or facilitate an ethical, meaningful, productive, and respectful collaboration between Settler researchers and Indigenous People engaged in community or regional monitoring programs? How can I bring Settler research and Indigenous knowledge systems together to facilitate more equitable and proactive environmental monitoring programs? My research examines the connections between community-based environmental monitoring, research ethics, and the role of social science in climate change adaptation programs. In this dissertation, I examine the context, community concerns and recommendations for research that emerged during my fieldwork, interviews, and workshops conducted in Pond Inlet and Cambridge Bay, Nunavut, and Calgary, Alberta. It is widely recognized that over the last few decades, the planet has been undergoing rapid climate change, particularly in the Arctic. Climate change has led to a discussion about the role of Settler research and Indigenous knowledge in understanding and addressing environmental changes and community and regional priorities. In the North of Canada and other Arctic regions, the role of Settler researchers facilitating ecological monitoring, environmental changes, and local and regional policy changes has been largely overlooked. As more Indigenous organizations and communities continue to advocate and demonstrate the validity of their knowledge systems, levels of government and research institutions seek to facilitate and embrace the co-integration Indigenous Knowledge (IK) and Settler research. At an individual level, the co-integration of IK with Settler research will build skills and promote community resilience brought on by climate change. At a societal level, the benefits and potential of integrating IK with Settler research are a resource that needs to be investigated. It can add new and essential aspects to climate change adaptation strategies. However, it can also be problematic and reproduce already ...